PEMODELAN TOMOGRAFI CROSS-HOLE METODE GEOLISTRIK RESISTIVITAS (Bentuk Anomali Silindris) - Prabowo, Riza Eka; Yulianto, Gatot; Nurwidyanto, M. Irham (BERKALA FISIKA, 2006)
Cross-hole method using an amount of electrode were placed downhole is one of tomography method. Cross-hole tomography method delineate the geological conditions of the earth surface therefore it takes an important rule in the case of anomaly monitoring. The buis concrete planted in subsurface with deepness of about 1 m were used as the source of anomaly. Tomography cross-hole data with configuration such as pole-pole, pole-bipole, bipole-pole and bipole-bipole array were taken with the depth of the borehole is 1,2 m. The space variation of one electrode to another in the hole of drill is 0,2 m, 0,4 m, 0,6 m and 0,8 m for the configuration of pole-bipole, bipole-pole and bipole-bipole. Res2Dinv program obtained the images of bipole-bipole better than the images of other configuration. While the pole-pole configuration had the worst images compared to others. It is caused by two remote electrode of pole-pole array while bipole-bipole array do not have ones. Key words: cross-hole, tomography, borehole, remote electrode